Starch structure and digestibility of rice high in resistant starch - Shu, Xiaoli; Jiao, Guiai; Fitzgerald, Melissa A.; Yang, Chaozhu; Shu, Qingyao; Wu, Dianxing (Wiley, 2006)
Starch digestibility and starch structure of a high‐resistant starch (RS) rice (RS111) was compared to that of a wild rice type (R7954). RS111 exhibited high RS content and incomplete starch hydrolysis in both cooked rice and retrograded rice flour. High RS rice RS111 had a higher λmax of absorbance and blue value of iodine‐binding starch complex and contained a higher percentage of intermediate chains of amylopectin than R/954. X‐ray diffraction pattern of RS isolated from cooked high RS rice displayed a mixture of B‐ and V‐type that was more resistant to starch hydrolysis by alpha‐amylase. Resistant starch in RS111 is composed mainly of linear amylose and some low‐molecular‐weight amylopectin.